A cost analysis of the U.S. Air Force overseas posture : informing strategic choices - Mills, Patrick, 1975-; Grissom, Adam; Kavanagh, Jennifer, 1981-; Mahnad, Leila; Worman, Stephen M. (Research report (Rand Corporation), 2013)
This report seeks to inform the debate over the extent of U.S. military presence overseas by providing a rigorous estimate of the costs associated with maintaining U.S. Air Force installations and units overseas rather than in the United States. The authors describe the various types of expenditures required to maintain bases and military units overseas and estimate current costs using official data and econometric modeling. They provide a cost model of overseas presence for policymakers to weigh alternative posture options. Their main findings are that while it does cost more to maintain force structures and installations overseas rather than in the United States, the total cost of doing so for the Air Force's current overseas posture is small relative to the Air Force's overall budget.